UPAYA MENINGKATKAN PEMAHAMAN KONSEP IPA SISWA DENGAN METODE EKSPERIMEN DI SEKOLAH DASAR (SD) - nur hasanah, siti maskanah; Din Azwar Uswatun; Lutfi Hamdani Maula (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low understanding of science concepts among fourth-grade students at Tipar State Elementary School, Sukabumi Regency, which is caused by the teacher-centered learning process, which tends to make students passive. This study aims to improve students' understanding of science concepts through the application of experimental methods. The type of research used is Participant Classroom Action Research (CAR) which is carried out collaboratively in two cycles. The research design used is the Kemmis and Mc Taggart model, which is carried out in two cycles. Each cycle consists of four stages: planning, action, observation, and reflection. The subjects of this study were 20 fourth-grade students at Tipar State Elementary School. Data collection techniques used performance tests (practice), observation, field notes, and documentation. The results of the study showed an increase in teacher activity from an average score of 73 (sufficient) in cycle I to 85 (good) in cycle II. Student activity also increased from an average score of 74 (sufficient) in cycle I to 81 (good) in cycle II. The improvement in students' understanding of science concepts is evident in the significant increase in the percentage of classical completion, from 55% (11 students) in cycle I to 80% (16 students) in cycle II. Therefore, it can be concluded that the application of the experimental method has proven effective in improving students' understanding of science concepts in elementary schools. Keywords: Experimental Method, Understanding of Science Concepts, Elementary School.